1978
DOI: 10.1152/ajprenal.1978.235.6.f570
|View full text |Cite
|
Sign up to set email alerts
|

Renal histamine H1 and H2 receptors: characterization and functional significance

Abstract: Canine experiments were designed to determine if both histamine H1 and H2 receptors are present in the renal circulation. Renal blood flow (RBF) increased steeply over the first minute of intra-arterial histamine infusion, then increased gradually to a plateau in 3--5 min. Infusion of either histamine + H2 antagonist or of H1 agonist produced the initial rapid increase in RBF, whereas infusion of either histamine + H1 antagonist or of H2 antagonist produced a slower but more sustained increase in RBF. Histamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 0 publications
6
30
0
Order By: Relevance
“…In the kidney of diabetic rats, histamine was increased compared with controls [2]. Basically, histamine has been reported to regulate the renal microcirculation, to increase salt and water excretion [3][4][5], decrease the ultrafiltration coefficient by reducing the total filtration surface area [4], and increase renin release [6].…”
Section: Introductionmentioning
confidence: 98%
“…In the kidney of diabetic rats, histamine was increased compared with controls [2]. Basically, histamine has been reported to regulate the renal microcirculation, to increase salt and water excretion [3][4][5], decrease the ultrafiltration coefficient by reducing the total filtration surface area [4], and increase renin release [6].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, in the kidney of diabetic rats, histamine was increased compared with controls [6,7]. Independent studies indicate that histamine regulates the renal microcirculation, by increasing salt and water excretion [8][9][10], decreasing the ultrafiltration coefficient by reducing the total filtration surface area [10], and increasing renin release [11].…”
Section: Introductionmentioning
confidence: 99%
“…In in vivo studies, infusion of histamine into the renal arteries of dogs resulted in renal vasodilatation, diuresis, natriuresis but no change in glomerular filtration rate (O'Brien & Williamson, 1971). Recently Banks, Fondacaro, Schwaiger & Jacobson (1978) have demonstrated that the renal vasculature contains both Hl-and H2-receptors and that these receptors have different effects on renal function even though both receptors are involved in renal vasodilatation.…”
Section: Introductionmentioning
confidence: 99%